The value of transesophageal echocardiography in the investigation and management of cryptogenic cerebral ischemia: a single-center experience - Katsanos, Aristeidis H; Patsouras, Dimitrios; Tsivgoulis, Georgios; Kosmidou, Maria; Katsanos, Konstantinos H; Kyritsis, Athanassios P; Giannopoulos, Sotirios (Neurological sciences, 2016)
The diagnostic utility of transesophageal echocardiography (TEE) has often been challenged in patients with cryptogenic stroke (CS). We estimated the prevalence of different findings on TEE examination of CS patients, their impact on secondary stroke prevention and the presence of potential age or gender disparities. We reviewed all TEE examinations that were performed in a single echocardiography laboratory during a 7-year-old period to identify CS patients that underwent investigation with TEE. Of the 518 total TEE examinations, we identified 88 CS patients. TEE revealed abnormal findings in 69.3 % of them. Patent foramen ovale (PFO) and atrial septal aneurysm (ASA) were identified in 30.6 and 22.7 % of the patients. Ascending aorta and aortic arch atheromatosis was present in 26.1 % of the patients, with complex atheromatosis diagnosed in 14.7 % of them. Cardiac myxomas were uncovered in 2.3 %. Thrombi in the left atrium and in cardiac valves were reported in 3.4 and 2.3 % of the patients, respectively. Based on TEE findings, the therapeutic management would be very likely modified in 9.1 % of the patients. Subgroup analysis revealed no gender disparities on the prevalence of TEE findings and in secondary stroke prevention, while linear regression analyses revealed significant associations of age with the prevalence of PFO, ASA, aorta atheromatosis and complex aorta atheromatosis. TEE examination should be included in the diagnostic work-up of all CS patients, irrespective of age and gender status, since it can reveal potential sources of embolism and has a significant impact for secondary stroke prevention.
Keywords: Cryptogenic stroke; Patent foramen ovale; lineární modely; nemoci aorty; ischemie mozku; Brain Ischemia; Humans; foramen ovale apertum; lidé středního věku; Stroke; prevalence; Female; věkové faktory; lidé; aterosklerotický plát; Foramen Ovale, Patent; cévní mozková příhoda; Anticoagulation; ženské pohlaví; Aortic Diseases; Male; Echocardiography, Transesophageal; Middle Aged; sekundární prevence; Retrospective Studies; Linear Models; Sex Characteristics; pohlavní dimorfismus; echokardiografie transezofageální; Prevalence; retrospektivní studie; Age Factors; mužské pohlaví; Plaque, Atherosclerotic; Transesophageal echocardiography; Aorta atheromatosis; Secondary Prevention